Near-infrared Polarimetry and H2 Emission toward Massive Young Stars: Discovery of a Bipolar Outflow Associated to S235 e2s3 - R. Devaraj; A. Caratti o Garatti; L. K. Dewangan; R. Fedriani; T. P. Ray; A. Luna (The Astrophysical Journal, 2023)
We present a near-infrared H- band polarimetric study toward the S235 e2s3 protostar, obtained using the POLICAN instrument on the 2.1 m OAGH telescope. The images reveal a bipolar outflow with a total length of about 0.5 pc. The outflow nebulosity presents a high degree of linear polarization (∼80%) and reveals a centrosymmetric pattern with the polarization position angles. The polarization characteristics suggest their origin to be single scattering associated with dust in the outflow. Using multiwavelength archival data, we performed spectral energy distribution (SED) fitting based on radiative transfer models of turbulent core accretion theory. The best-fit SED model indicated that the protostar has a mass of 6.8 ± 1.2 M _⊙ , with a disk accretion rate of 3.6 ± 1.2 × 10 ^−4 M _⊙ yr ^−1 and a total bolometric luminosity of 9.63 ± 2.1 × 10 ^3 L _⊙ . Narrowband H _2 (2.12 μ m) observations show shocked emission along the bipolar lobes tracing the jet’s interaction with the surrounding medium. The estimated H _2 luminosity of the outflow is ${2.3}_{-1.3}^{+3.5}\,L_{\odot }$ , which matched the known power-law correlation with the source bolometric luminosity, similar to other high-mass outflows. The orientation of the bipolar outflow was found to be parallel to the local magnetic field direction. The overall results assert the fact that the S235 e2s3 source is a massive young star driving a highly collimated bipolar outflow through disk accretion.